Restorative Justice On Death Caused By Traffic Accident - Zulkifli Mohamad (Estudiante Law Journal, 2022)
This study aims to determine how the application of Restorative Justice to Traffic Accidents That Cause Death. An empirical research method that serves to see the law in a real sense and examines how the law works in the community. The data collection process used interview techniques and direct data collection at the Gorontalo City Police Traffic Unit Office. This study uses a qualitative method by describing it descriptively. The results showed that many cases were not processed to the Gorontalo District Court because there were several factors, namely, Not getting sufficient evidence, the accident that occurred was not a crime, the perpetrator of the accident died, the perpetrator of the accident was still a minor, The family of the accident victim who has been sincere, and the family of the victim who does not want to deal with the court because it takes a long time and the criminal case has expired. Regarding efforts to resolve cases of traffic accidents that result in death, namely ADR (Alternative Dispute Resolution), Diversion, and SP3 (Termination of Investigation).